2012
DOI: 10.1007/s00024-012-0557-6
|View full text |Cite
|
Sign up to set email alerts
|

Curie Point Depth Estimates from Aeromagnetic Data from Death Valley and Surrounding Regions, California

Abstract: Aeromagnetic data were analyzed to determine the Curie point depth (CPD) by power density spectral and threedimensional inversion methods within and surrounding Death Valley in southern California. We calculated the CPD for 0.5°r egions using 2D power density spectral methods and found that the CPDs varied between 8 and 17 km. However, the 0.5°region may average areas that include shallow and deep CPDs, and because of this limitation, we used the 3D inversion method to determine if this method may provide bett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 42 publications
(71 reference statements)
2
19
0
1
Order By: Relevance
“…Hussein et al . [] used the power spectral analysis method to estimate CPD from magnetic data covering the Death Valley in the Western U.S. and showed that the maximum depth of the imaged anomaly source is approximately one third to one fourth of the width of the subregion used in the analysis. Therefore, we selected the subregion size to be 1° × 1° to ensure imaging of the Moho found at depths expected for tectonic settings such as the ORZ and surroundings.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Hussein et al . [] used the power spectral analysis method to estimate CPD from magnetic data covering the Death Valley in the Western U.S. and showed that the maximum depth of the imaged anomaly source is approximately one third to one fourth of the width of the subregion used in the analysis. Therefore, we selected the subregion size to be 1° × 1° to ensure imaging of the Moho found at depths expected for tectonic settings such as the ORZ and surroundings.…”
Section: Methodsmentioning
confidence: 99%
“…Traditionally, the CPD is determined using 2‐D spectral methods [ Spector and Grant , ; Byerly and Stolt , ; Shuey et al ., ; Bhattacharyya and Leu , ; Okubo et al ., ; Tanaka et al ., ; Ross et al ., ; Hussein et al ., ; Arnaiz‐Rodrigues and Orihuela , ]. This method has been used successfully to determine the regional CPD values over large study areas [e.g., Blakely , ; Ross et al ., ; Hussein et al ., ; Arnaiz‐Rodrigues and Orihuela , ]. The major drawback associated with the 2‐D spectral method is the incorporation of local horizontal variations (<15 km) in the CPD values.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations